IN VITRO INDUCTION OF YACON TUBEROUS ROOT AND IDENTIFICATION OF GENES ASSOCIATED WITH TUBEROUS ROOT EXPANSION - Y. Duan; T. Xue; J. Li; J. Teng; A. Zhang; W. Sheng; Y. Zhu; L. Chang; J. Xue (Journal of Animal and Plant Sciences, 2015)
Yacon (Smallanthussonchifolius) has become increasingly popular worldwide owing to the nutritional and prebiotic function of its tuberous root. Elucidating the molecular mechanism controlling the expansion of the tuberous root in yacon is important for its breeding and in vitromanipulation. However, both the in vitro induction and the development mechanism of yacon tuberous root are still unclear. In this study, we optimized the medium formula for efficient induction of tuberous root in vitro from leaf-derived adventitious roots using an orthogonal design. The optimal medium for in vivo tuberous root initiation was determined as Murashige and Skoog medium supplemented with 3 mgL-1 6-benzylaminopurine, 0.1 mgL-1 naphthalene acetic acid, and 70 gL-1 sucrose. Suppression subtractive hybridization (SSH) was performed to identify the transcripts up-regulated during the expansion of yacon tuberous root. The cDNAs of expanded and unexpanded tuberous roots were used as the ‘tester’, and ‘driver’, respectively. SSH library sequencing yielded 302 expressed sequence tags (ESTs). Finally, 97 ESTs were retained after screening, 15 of which had no significant homology to any of the previously identified genes. Real-time quantitative RT-PCR analysis of the expression patterns showed that all 11 transcripts were up-regulated during the tuberous root expansion process. These ESTs were highly homologous with expansion, β-xyloglucan endotransglycosylase, acyl-CoA-binding protein, asparagine synthetase, seed storage protein, lignin-related peroxidase, cytochrome P450, polyubiquitin, translation initiation factor, and nutrient storage protein. These results would facilitate the functional characterization of the genes associated with yacon tuber expansion and subsequent in vitromanipulation.
Keywords: in vitromanipulation; Smallanthussonchifolius; suppression subtractive hybridization; tuberous root expansion